Ecology and Justice: From Environmental Justice to Integral Ecology of «Laudato si’» - Gocko, Jerzy (Studia Ecologiae et Bioethicae, 2024)
Until recently, in the social teaching of the Church, the principle of social justice has been primarily related to issues of poverty, social inequalities, wealth distribution, and goods. Pope Francis extends this understanding to environmental issues. While diagnosing and describing the contemporary ecological crisis (our inability to resolve it in particular), he identifies the same mindset and mechanisms underlying both the social and ecological crises. Pope Francis's encyclical Laudato si’ is, therefore, a revolutionary text, which, based on integral ecology, reintroduces justice (similarly to Rerum Novarum over 130 years ago) as the key to addressing a new social issue – the contemporary ecological crisis. The comprehensive perspective on the contemporary global crisis as a socio-ecological crisis, in Laudato si’ finds its reference in the developed concept of Environmental Justice – an ecological justice as a new type of social justice. The viewpoint of a moral theologian allows us to perceive the duties associated with it not only as a legal obligation (debitum iuridicum) but also more deeply as a moral obligation (debitum morale).